PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS KELAS PADA MATA PELAJARAN BIOLOGI SMA KELAS X - Wilasari Arien; Evi Suryawati; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The purpose of this research is to develop the classroom-based assessmenton biology subjects for X grade Senior high school. Classroom-based assessmentinclude paper and pencil test, attitude assessment, performance assessment, productassessment, project assessment, self-assessment and portofolio assessment. Thedevelopment was conducted at Biology Education University of Riau and the limitingtest was conducted at MAN 2 Model Pekanbaru. The research held on January untilApril 2014. Research and Development (R & D) with ADDIE model was implementedin this research. Subjects consisted of four Basic-Competency on the X grade seniorhigh school. Validation sheet was used as the data collection instrument. Thisvalidation sheet was filled by the internal dan external validator. Collected datas wereanalyzed by descriptive statistics. Average results of the validity of class-basedassessment are: 3.6 for the paper and pencil test, 3.7 for attitude assessment, 3.7 forperformance assessment, 3.6 for product assessment, 3.6 for project assessment, 3.8 forself-assessment and 3.7 for portofolio assessment. On the last stage of the research, alimiting test on the X grade senior high school. Based on the research’s results can beconcluded that the development of classroom-based assessment on biology science for Xgrade senior high school student was done with the ADDIE model that consists of somephase, start from analyze, design, develop, and the last is implementation in a limitingtest. Based on the results of validation, classroom-based assessment could beimplemented with the field test.Key words: biology senior high school, classroom-based assessment, development